Use of Face Mask as Visual Reminder of the Virus: Covid-19 and Frustration - Nabila Hassan, Najma Shaikh, Shagufta Magsi, Farhat Sultana, Samina Shaikh, Zakia Zaheen (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: Infection with COVID-19 is spreading as a droplet infection through the respiratory droplets of an infected person. Wearing a facemask, in addition to practicing social distancing and good hand hygiene, can help prevent the infection. The study determined the effect of fear of infection on the use of face masks and use of face mask to the frustration and to analyze the mediating effect of use of face masks between fear of infection and frustration. Methodology: Time horizon wise the study is cross-sectional where data collected first-hand for the research by adopting a convenience non-random sampling technique, where data collected by conducting a web-based survey consisting of the general public from Hyderabad city in November 2020. Using Smart PLS 3.0 software the significance and relevance of path coefficients testing performed the partial least square (PLS-SEM) approach. Results: Mean age of the individuals was 35.12+23.44 years and females were in majority 59.8%. The outer loadings and Composite Reliability (CR) are greater than 0.50 and 0.70 respectively ascertaining indicator reliability and internal consistency reliability. Convergent validity is maintained as AVE are above 0.5, indicated that discriminant validity is maintained as HTMT values are less than 0.85. Fear of infection is positively associated to use of facemask and use of facemask is positively associated with frustration and use of facemask has an indirect relationship with fear of infection and frustration. Conclusion: It was concluded that the effect of fear of infection from coronavirus will increase the use of facemask. It also analyzed the annoyance caused by wearing a face mask and has highlighted the mediational effect of face mask use between the fear of infection and frustration.